KARAKTERISTIK KEPEMIMPINAN UNTUK MENINGKATKAN KETERLIBATAN KARYAWAN DALAM STARTUP TAHAP AWAL - Fazira Zia; Anggara Wisesa; Irka Wijaya (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The survey shows that 65% of startup failures are caused by leaders and also low engagement in the company. Therefore, this research was conducted to find out what characteristics a leader should have and how to implement these characteristics to increase engagement at his startup. The research used a qualitative approach focusing on multiple case studies as a method with the aim of gaining individual and group experience. To answer the research objective, two early-stage startups were selected along with six informants and in-depth interviews were conducted. Data analysis was started with a coding procedure from open to selective coding and ended with pattern matching analysis. From the analysis, it was found five leadership characteristics in the early-stage startups that must be possessed by a leader to increase employee engagement: (1) Influence; (2) Firm; (3) Intelligence; (4) Democracy; (5) Inspire. Each characteristic has its own practical example of how the leader can implement these characteristics in real cases, so it can enhance organizational performance indirectly.